2021
DOI: 10.3389/fphar.2021.621300
|View full text |Cite
|
Sign up to set email alerts
|

Role of NLRP3 Inflammasome in Lupus Nephritis and Therapeutic Targeting by Phytochemicals

Abstract: Systemic lupus erythematosus (SLE) is a multisystem autoimmune inflammatory condition that affects multiple organs and provokes extensive and severe clinical manifestations. Lupus nephritis (LN) is one of the main clinical manifestations of SLE. It refers to the deposition of immune complexes in the glomeruli, which cause kidney inflammation. Although LN seriously affects prognosis and represents a key factor of disability and death in SLE patients, its mechanism remains unclear. The NACHT, leucine-rich repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 123 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…Moreover, NLRP3 inflammasome activation is induced by the NF-κB signaling pathway [ 61 ]. A growing number of studies have demonstrated the relationship between NLRP3 inflammasome activation and SLE [ 62 ]. Interestingly, inhibition of NLRP3 inflammasome activation ameliorates SLE disease in patients and SLE animal models [ 5 , 9 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NLRP3 inflammasome activation is induced by the NF-κB signaling pathway [ 61 ]. A growing number of studies have demonstrated the relationship between NLRP3 inflammasome activation and SLE [ 62 ]. Interestingly, inhibition of NLRP3 inflammasome activation ameliorates SLE disease in patients and SLE animal models [ 5 , 9 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…[41] Pyroptosis is a type of programmed cell death that is associated with the inflammasome. [42] LPS has been reported to induce NLRP3dependent pyroptosis by promoting ROS production in H9C2 cells. [43] Further reports pointed out that OTA could induce nephritis and renal fibrosis through the activation of NLRP3-dependent pyroptosis in MDCK cells and mice.…”
Section: Discussionmentioning
confidence: 99%
“…The NLRP3 inflammasome contribute to tissue damage in lupus nephritis [ 137 ]. Studies have shown that the NLRP3 inflammasome is upregulated in lupus nephritis patients and that its inhibition can ameliorate kidney injury in animal models of lupus nephritis [ 137 , 138 ]. Moreover, dysregulated lipid metabolism has also been implicated in the pathogenesis of lupus nephritis.…”
Section: The Impact Of Immunometabolic Dysregulation In Kidney Diseasementioning
confidence: 99%